2018
DOI: 10.1177/1044389418782429
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Physical and Emotional Sibling Violence: A Potential Connection to Elder Abuse

Abstract: This article focuses on the persistence of physical and emotional sibling violence through the life course and its potential connection to elder abuse. Theories relevant to the linkage between sibling violence and elder abuse are presented and discussed. Highlighted is the need for future studies to examine the association between these forms of family violence in order for preventative and intervention mechanisms to be created and implemented. Implications for practice include the need to assess physical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The need to examine the connection between PESV and attachment in adulthood has been noted and implied previously (Meyers, 2016;Perkins et al, 2018). Some studies have specifically examined connections between sibling violence and attachment (Lee et al, 2014;Tibbetts & Scharfe, 2015;Walters et al, 2020), yet these studies focused on youth and young adulthood.…”
Section: Sibling Violence and Adult Attachmentmentioning
confidence: 99%
“…The need to examine the connection between PESV and attachment in adulthood has been noted and implied previously (Meyers, 2016;Perkins et al, 2018). Some studies have specifically examined connections between sibling violence and attachment (Lee et al, 2014;Tibbetts & Scharfe, 2015;Walters et al, 2020), yet these studies focused on youth and young adulthood.…”
Section: Sibling Violence and Adult Attachmentmentioning
confidence: 99%
“…Previously, in Wiehe's (1998) study, adult sibling survivors reported that the way siblings treated them was similar to the way parents treated them. More recently, Perkins, Spira, and Key (2018) used social learning theory to explore the link between sibling abuse and later elder abuse. The authors explored in a case study how sibling violence may increase the risk of elder abuse, as Wiehe (1997) has also argued, suggesting intergenerational transmission of family violence.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Although the problem of elder abuse may not seem relevant to the issue of sibling violence, caregivers may be siblings, or as noted in the discussion above regarding the consequences of sibling violence in adulthood, abuse between adult siblings and/or unresolved issues from childhood violence between siblings may affect the well-being of an elderly parent (Perkins, Spira, & Key, 2018). Thus, legislation focused on the issue of elder abuse could potentially be one policy venue for addressing the issue albeit in later life.…”
Section: Elder Abusementioning
confidence: 99%